Review on the Diverse Biological Effects of Glabridin - Zhang J; Wu X; Zhong B; Liao Q; Wang X; Xie Y; He X (Drug Design, Development and Therapy, 2023)
Jianhong Zhang,1,2,* Xinhui Wu,3,* Baiyin Zhong,1,* Qicheng Liao,1 Xin Wang,1 Yuankang Xie,1 Xiao He1 1Department of Hepatobiliary Surgery, First Affiliated Hospital of Gannan Medical University, Ganzhou, 341000, People’s Republic of China; 2Ganzhou Key Laboratory of Hepatocellular Carcinoma, First Affiliated Hospital of Gannan Medical University, Ganzhou, 341000, People’s Republic of China; 3Department of General Surgery, The First Affiliated Hospital of Gannan Medical University, Ganzhou, 341000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiao He, Email hexiao@gmu.edu.cnAbstract: Glabridin is a prenylated isoflavan from the roots of Glycyrrhiza glabra Linne and has posed great impact on the areas of drug development and medicine, due to various biological properties such as anti-inflammation, anti-oxidation, anti-tumor, anti-microorganism, bone protection, cardiovascular protection, neuroprotection, hepatoprotection, anti-obesity, and anti-diabetes. Many signaling pathways, including NF-κB, MAPK, Wnt/β-catenin, ERα/SRC-1, PI3K/AKT, and AMPK, have been implicated in the regulatory activities of glabridin. Interestingly, glabridin has been considered as an inhibitor of tyrosinase, P-glycoprotein (P-gp), and CYP2E1 and an activator of peroxisome proliferator-activated receptor γ (PPARγ), although their molecular regulating mechanisms still need further investigation. However, poor water solubility and low bioavailability have greatly limited the clinical applications of glabridin. Hopefully, several effective strategies, such as nanoemulsions, microneedles, and smartPearls formulation, have been developed for improvement.Graphical Abstract: Keywords: glabridin, tyrosinase inhibitor, P-gp, anti-inflammation, anti-oxidation, anti-microorganism